Occurrence of Extended Spectrum β-Lactamases, KPC-Type, and MCR-1.2-Producing Enterobacteriaceae from Wells, River Water, and Wastewater Treatment Plants in Oltrepò Pavese Area, Northern Italy - Caltagirone, Mariasofia; Nucleo, Elisabetta; Spalla, Melissa; Zara, Francesca; Novazzi, Federica; Marchetti, Vittoria M.; Piazza, Aurora; Bitar, Ibrahim; De Cicco, Marica; Paolucci, Stefania; Pilla, Giorgio; Migliavacca, Roberta; et al. (Frontiers in Microbiology, 2017)
To evaluate the water compartment antibiotic-resistance contamination rates, 11 wells, five streams and four treatment plants located in the Oltrepò Pavese area were screened for the presence of third generation cephalosporins resistant Gram-negative bacteria. Enterobacteriaceae were also characterized for the Extended-Spectrum-β-Lactamases (ESBLs), carbapenemases and mcr-1 genes presence. From December 2014 to November 2015, 246 water samples were filtered, plated on Plate Count Agar, MacConkey Agar and MacConkey Agar with cefotaxime. Isolates were species identified using AutoSCAN-4-System and ESBLs, carbapenemases and colistin resistance determinants were characterized by PCR, sequencing and microarray. Plasmid conjugative transfer experiments, PCR-based Replicon typing, Pulsed-Field Gel Electrophoresis, Multi-Locus-Sequence-Typing and in-silico plasmid characterization were performed. A total of 132 enterobacteria isolates grew on MacConkey agar with cefotaxime: 82 (62.1%) were obtained from streams, 41 (31.1%) from treatment plants, and nine (6.8%) from wells. Thirty out of 132 (22.7%) isolates, mainly belonging to Escherichia coli (n=15) species, showed a synergic effect with piperacillin-tazobactam. A single ESBL gene of blaCTX-M-type was identified in 19/30 isolates. In further two E. coli strains, a blaCTX-M-1 gene co-existed with a blaSHV-type ESBL determinant. A blaSHV-12 gene was detected in two isolates of E. coli (n=1) and Klebsiella oxytoca (n=1), while any ESBL determinant was ascertained in seven Yersinia enterocolitica strains. A blaDHA-type gene was detected in a cefoxitin resistant Y. enterocolitica from a stream. Interestingly, two Klebsiella pneumoniae strains of ST307 and ST258, collected from a well and a wastewater treatment plant, resulted KPC-2 and KPC-3 producers, respectively. Moreover, we report the first detection of mcr-1.2 ST10 E. coli on a conjugative IncX4 plasmid (33.303bp in size) from a stream of Oltrepò Pavese (Northern Italy). Both ESBLs E. coli and ESBLs/carbapenemase-producing K. pneumoniae strains showed clonal heterogeneity by Pulsed-Field Gel Electrophoresis and Multi-Locus-Sequence-Typing. During one-year study and taking in account the whole Gram-negative bacterial population, an average percentage of cefotaxime resistance of 69% 32% and 10.3% has been obtained for the wastewater treatment plants, streams and wells, respectively. These results, of concern for public health, highlight the need to improve hygienic measures to reduce the load of discharged bacteria with emerging resistance mechanisms.